Analysis of the Impact of the Existence of Tano Tubu Office on the Emergence of a New Community Business Sector - Dirman Sihombing; Sirojuzilam Sirojuzilam; Badaruddin Badaruddin (Budapest International Research and Critics University, 2020)
The aims of this study is to analysis the impact of existence of Tano Tubu Office on the Emergence of a New Community Business Sector. This study uses a descriptive method with a quantitative approach. The result shows that there is a difference between the average income of business people around the Tano Tubu Office in the period before the Tano Tubu office and after the Tano Tubu office. The average income in the period before the establishment of the Tano Tubu Office was Rp. 2,163,382.93, - , while the average value of income in the period after the establishment of Tano Tubu Office was Rp. 4,183,333.33 ,. The existence of Tano Tubu Offices has a positive impact on increasing the income of the business community around it. This is indicated by the higher average income in the period after the establishment of Tano Tubu Office compared to the average income in the period before the establishment of Tano Tubu Office.